PERPUSTAKAAN ANAK DI ERA DIGITAL - Muzdhalifah Muzdhalifah (Jurnal Pustaka Ilmiah, 2019)
In this day and age is a modern era, in Indonesia, the children’s library has begun to emerge in order to introduce the library to children as early as possible, to provide stimulus to children so that when children are teenagers they will be accustomed to hearing the words of childbirth. the book itself is a source of knowledge. Apart from that, children in the modern era are always introduced and given several facilities, such as attractive interior design, interior arrangements that are suitable for children so that children are interested in visiting the library, and the appropriate composition of books and services for children is also different from those available in traditional libraries, this paper will discuss children’s libraries in the modern era in terms of interiors, services, and also interior settings. This writing is only a description of the existing children’s institutions in Indonesia. It is expected that the presence of the library can foster a sense of love for children, and introduce an interesting library (modern era) and eliminate the impression of a rigid (traditional) library. The approach in this study is a qualitative approach with the method of collecting data looking at the results of previous studies then analyzed.Keywords : Children’s library, digital era.